Patients from the Oral Oncology Center, UNESP, Araçatuba with an indication for prosthesis - Pesqueira, Aldiéris Alves [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Moreno, Amália [UNESP]; Haddad, Marcela Filié [UNESP]; Ribeiro, Paula do Prado [UNESP]; Bannwart, Lisiane Cristina [UNESP]; Miyahara, Glauco Issamu [UNESP] (Molecular and Clinical Oncology, 2013)
Head and neck tumors are a major health concern worldwide, due to their high incidence and mortality rates, particularly in developing countries. In Brazil, this type of cancer is commonly diagnosed and studies suggested that it may be the leading cause of mortality in the country. The increase in life expectancy worldwide, as well as environmental and behavioral factors, are related to carcinogenesis. Therefore, an understanding of basic epidemiology and statistical methods is critical, in order to promote early diagnosis and cancer prevention. Cancer patients with an indication for prosthesis were selected from the medical records of the Oral Oncology Center, School of Dentistry, São Paulo State University (UNESP), Araçatuba, between 1991 and 2010. The following variables were recorded: gender, age, type and location of the lesion, radiation dose and dental prosthesis. The majority of the patients were male (74.15%) and >60 years of age (53.37%). Tumors were most commonly located in the floor of the mouth (11.1%) and squamous cell carcinoma was the most prevalent type (72.8%). This study provides the profiles of patients who attended the Oral Oncology Center and the results may aid in the creation of cancer prevention programs.
Keywords: Age groups; Gender identity; Head and neck neoplasms; Neoplasms by site; Quality of life